The Interpretation of The Turan Eneolitic Period in Iranian Historiography: Analysis and Prospects (Texas Journal of Philology, Culture and History, 2025)
This article provides a historiographical analysis of the role and perspectives of the modern Iranian school of archaeology in the study of the Eneolithic (Chalcolithic) period in Central Asia, particularly in the ancient territory of Turan. The article comprehensively examines the concepts of Iranian scholars regarding the periodization and chronology of the region's Eneolithic era, the interpretation of the evolution of material culture (pottery, architecture), and the processes of cultural contact and migration. The main focus is on the theories of leading Iranian researchers such as Seyed Mansour Sajjadi and Hasan Fazeli, as well as their relationship with the scientific conclusions of Soviet and Western archaeologists. The purpose of this article is to assess the contribution of Iranian historiography to the scientific debates on the Turan Eneolithic and to outline future research directions in this field.